KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI SEKOLAH DASAR PADA ERA DIGITAL - Nur Efendi (JIPDAS (Jurnal Ilmiah Pendidikan Dasar), 2025)
This study aims to analyze the role of transformational leadership of the school principal in improving the quality of learning in the digital era at SD Islam Al Azhar Tulungagung. The study employs a qualitative approach with a case study design focusing on leadership practices, their impact on learning, and implementation challenges. Data were collected through in-depth interviews, classroom observations, and document analysis. The findings indicate that the principal implements transformational leadership by strengthening a digital-oriented vision, empowering teachers, and fostering a collaborative culture. The impact is reflected in increased teacher creativity in utilizing technology, higher student engagement in learning activities, and more dynamic classroom interactions. The challenges include gaps in teachers’ digital literacy, limited infrastructure, and increased workload. Adaptive leadership addresses these barriers through continuous professional development and effective resource management. The findings reveal that transformational leadership contributes significantly to improving the quality of learning in primary education in the digital era.